Effects of (Pro)renin Receptor on Diabetic Cardiomyopathy Pathological Processes in Rats via the PRR-AMPK-YAP Pathway - Xiong, Jie; Dong, Xuefei; Li, Shengnan; Jiang, Fan; Chen, Jing; Yu, Shiran; Dong, Bo; Su, Qing (Frontiers in Physiology, 2021)
Diabetic cardiomyopathy (DCM) is a common complication associated with diabetes. The (pro)renin receptor (PRR) is an important member of the local tissue renin-angiotensin system and plays a vital role in many cardiovascular diseases. Yes-associated protein (YAP) also plays a crucial role in many cardiovascular diseases. However, the mechanism responsible for the effects of PRR and YAP on DCM remains unclear. The purpose of this study was to determine the role of PRR in the pathological progression of DCM and whether PRR influences the pathological processes of diabetic cardiomyopathy through YAP. We first established diabetic cardiomyopathy rats model, downregulated the expression of PRR, and upregulated and downregulated the expression of YAP. The levels of myocardial inflammation and fibrosis were then measured and cardiac function was evaluated. In vitro, primary rat cardiac fibroblasts (CFs) were cultured with high glucose, with or without transfection with recombinant adenovirus expressing PRR, and GSK621 was used to observe the effect of AMPK. The levels of inflammation and fibrosis were measured in vitro. The results showed that PRR and YAP silencing alleviated myocardial inflammation and fibrosis. GSK621 blocked the effect of PRR on AMPK and YAP and improved CF inflammation and fibrosis. The inhibition of PRR expression offers a new therapeutic strategy for the treatment of DCM. The effects of PRR on the pathological process of DCM in rats may be mediated via the PRR-AMPK-YAP pathway.